RECRYSTALLIZED AGGLOMERATES OF INDOMETHACIN BY EMULSION SOLVENT DIFFUSION (ESD) TECHNIQUE. - V.B.YADAV; A.V.YADAV (International Journal of Pharma and Bio Sciences, 2010)
The aim of present study was to prepare and characterize the recrystallized agglomerates of water insoluble non steroidal anti-inflammatory drug, indomethacin (IM) with hydrophilic polymers like polyvinyl pyrrolidone (PVP),hydroxyl ethyl cellulose (HEC) and hydroxyl propyl methyl cellulose (HPMC) by using emulsion solvent diffusion (ESD) technique for enhancing the solubility, dissolution rate,flowability,wettability and Packability of IM. The ESD technique employed three test solvents: first substance dissolution medium-good solvent (methanol); second partial dissolution medium for the substance-bridging liquid (dichloromethane) and third poor solvent for drug substance (distilled water).X-ray powder diffractometry (XRPD) and differential scanning calorimetry (DSC) were performed to examine the physical state of the IM and prepared recrystallized agglomerates. DSC thermograms showed the changes in melting peak of the IM in recrystallized agglomerates suggesting the change in crystallinity of IM. The XRD revealed a characteristic decrease in crystallinity. The solubility and dissolution studies demonstrated a marked increase in solubility and dissolution rate of recrystallized agglomerates as compared to the pure IM drug. The recrystallized agglomerates enhanced the drug solubility and dissolution about 3 and 2 folds with HPMC and HEC polymer respectively. The prepared spherical crystals with used polymers exhibited excellent physicochemical properties like flowability, packability, and wettability compared with the pure raw crystals of indomethacin.